Contribution of Russia in the development of greenfield banking in the Republic of Serbia - Božović Jelena; Milošević Andriana (Ekonomski Pogledi, 2014)
The base of the Serbian-Russian economic-trade cooperation consists of the development of cooperation in the field of economy, economics and military-political sphere. One of important ways of economic cooperation between Russia and Serbia relates to the banking sector. The best example which confirms such assessment is the entry of the Bank of Moscow and announcement of the entry of larger Russian banks in Serbia, such as Gazprom Bank. The paper in its methodological approach treats the crucial motives of the Greenfield investments in banking, with special reference to contribution to the development of the economic cooperation between Russia and Serbia. The content-related treatment of the paper refers to the qualitative and quantitative aspects of the analysis of the Russian Greenfield banking in Serbia, while the recommendation for the development of the Greenfield investments in the country is presented in the conclusion.